TP53 mutations are infrequent in newly diagnosed chronic lymphocytic leukimia - Zainuddin, Norafiza; Murray, Fiona; Kanduri, Meena; Gunnarsson, Rebeqa; E. Smedby, Karin; Enblad, Gunilla; Jurlander, Jesper; Juliusson, Gunnar; Rosenquist, Richard (Pergamon, 2011)
TP53 mutations in the absence of 17p-deletion correlate with rapid disease progression and poor survival in chronic lymphocytic leukemia (CLL). Herein, we determined the TP53 mutation frequency in 268 newly diagnosed CLL patients from a population-based material. Overall, we detected TP53 mutations in 3.7% of patients (n = 10), where 7/10 cases showed a concomitant 17p-deletion, confirming the high prevalence of TP53 mutation in 17p-deleted patients. Only 3 (1.1%) of the newly diagnosed patients in our cohort thereby carried TP53 mutations without 17p-deletion, a frequency that is much lower than previous reports on referral cohorts (3–6%). Our findings imply that TP53 mutations are rare at CLL onset and instead may arise during disease progression.